Strategi BPOM dalam upaya mengatasi Pemberantasan dan Penyalahgunaan obat Ilegal melalui Gerakan “Waspada Obat Ilegal” - siti qonaah qonaah; Heri Afianto (Universitas Bina Sarana Informatika, 2020)
The distribution of illegal drugs is a serious problem that not only occurs in Indonesia, but globally. In Indonesia, the Food and Drug Supervisory Agency (BPOM) noted the growth of illegal drug circulation in the last few years was quite high. The